The card counter [videorecording (DVD)] - Isaac, Oscar; Haddish, Tiffany, 1979-; Sheridan, Tye, 1996-; Dafoe, Willem (Universal Studios, 2021)
William Tell is a gambler and former serviceman who sets out to reform a young man seeking revenge on a mutual enemy from their past. Tell just wants to play cards. His spartan existence on the casino trail is shattered when he is approached by Cirk, a vulnerable and angry young man seeking help to execute his plan for revenge on a military colonel. Tell sees a chance at redemption through his relationship with Cirk.